2019
DOI: 10.31377/jdrssa.v4i1.553
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Activity on the Support and Enhance the Natural Behavior of Stem Cells and Chosen Physiological Variables for Players Athletics

Abstract: The CD34+ antigen is a single chain trans membrane glycoprotein, expressed on human hematopoietic stem and progenitor cells, endothelial progenitor cells, vascular endothelial cells, embryonic fibroblasts and some cells in fetal and adult nervous tissue. The antigen is absent in fully differentiated hematopoietic cells such as lymphocytes, monocytes and granulocytes, erythrocytes and platelets. Regular physical activity is related to lower rates of CVD, however the mechanisms underlying the benefits of exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Over the past centuries, diseases did not appear among humans in this widespread due to change many of the behaviors that people are accustomed to especially Egyptian old farmer which are in line with nature, including waking up early with the onset of light and eating breakfast foods that are produced from the environment, which may be characterized by a decline in the economic well value [7].…”
Section: Glandsmentioning
confidence: 99%
“…Over the past centuries, diseases did not appear among humans in this widespread due to change many of the behaviors that people are accustomed to especially Egyptian old farmer which are in line with nature, including waking up early with the onset of light and eating breakfast foods that are produced from the environment, which may be characterized by a decline in the economic well value [7].…”
Section: Glandsmentioning
confidence: 99%
“…However, it quickly returns to normal after the end of the physical exertion. (28) The researcher explains this increase in blood pressure after physical exertion as the result of the decrease in the amount of oxygen in the muscles of the athlete, which leads to an increase in the need to fill this deficiency by increasing the work of the heart to deliver sufficient amounts of blood loaded with oxygen and nutrients to the athlete's muscles to return to a normal state, especially after exercise ends, so we find the athlete breathing very quickly and through this increase in the heartbeat, the pressure will be generated on the walls of blood vessels, which is called oxygen blood pressure, and thus this increase will lead to collateral damage in the case of high pressure, including tissue damage as a result of the arrival of large amounts of oxygen to muscles irregularly. (29) Kiyici confirmed this, "There are many external influences on the formation of free radical, including inhalation of air containing oxygen at a concentration greater than normal."…”
Section: Oxygen Blood Pressurementioning
confidence: 99%
“…In the United States of America, for example, it was found that 84% of adolescents eat large quantities of fat, and that 91% of them largely eat saturated fat, and that the consumption of vegetables and fruits is very low about the daily need. (55,56) .…”
Section: Table (4): Frequencies Percentages and Ca2 Values Of The Study Sample Responses On The Fourth And Fi Fth Axis: General Correct Wmentioning
confidence: 99%